Intermittent recycle-integrated reactor-separator for production of well-defined non-digestible oligosaccharides from oat β-glucan - Nguyen, Hoang S.H.; Kaspereit, Malte; Sainio, Tuomo (Chemical Engineering Journal, 2021)
A recycle-integrated reactor-separator system was studied experimentally and based on simulations for the acid-catalyzed depolymerization of oat beta-glucan polysaccharide. The aim was to produce oligosaccharides with degree of polymerization in a narrow range (DP = 15–30). The reactor was operated intermittently at 80 °C. Batch chromatography with Sephadex G-25 size-exclusion gel was found suitable for the separation of product from reactants and impurities. Part of the reaction mixture was periodically withdrawn and fed to the separation column. Molar mass distributions in four chromatographic fractions (waste, recycle, product, impurities) were monitored with SEC-MALLS. Experiments with 4 h mean residence time showed that the reactor-separator achieved approximately 2.0 and 2.5 times higher yield and purity of target DP than a batch reactor. Dimensionless operating parameters and equipment design parameters were introduced for analyzing performance of intermittent reactor-separators. The simulations show that intermittent operation offers higher yield and product purity than continuous operation (CSTR and chromatographic separation) when mean residence time in the reactor is long. Continuous operation is better when productivity is maximized by using short mean residence time and low yield.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Beta-glucan; Depolymerization; Integrated process; Non-digestible oligosaccharides; Reactor-separator